Exploring the Reflection of Romantic Relationship Through Person Deixis in the After Movie - Pramesti, Ni Wayan Utari Diah; Parthama, I Gusti Ngurah; Malini, Ni Luh Nyoman Seri (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study explores person deixis whose context reflects a romantic relationship in the movie After. Person deixis is the use of personal pronouns usually used in a conversation. The purpose of this study is to explore the types of person deixis in the context of a romantic relationship using the Pragmatic theory proposed by Levinson (1983). Data were taken from the After movie and analyzed using documentation techniques and analyzed using descriptive qualitative methods. This study found three types of persons deixis: first person deixis, second person deixis and third person deixis. These findings indicate the importance of context in interpreting deixis and contribute to a deeper understanding of how language shapes and reflects the development of relationships in cinematic narratives.